Perfil epidemiológico das notificações de violência contra a criança e o adolescente no Estado de Minas Gerais, 2009 a 2010 - Almeida, Aline Evangelista de (2012)
Violence is a social and historical problem that affects society. In children and adolescents, its biopsychosocial consequences affect their growth and infant-juvenile development. The dimension of violence is still little known in Brazil, because data do not precisely translate the complexity of cases. Due to the magnitude of this aggravation the notification of cases became mandatory. The aims of this study were: describe the epidemiologic profile using notifications of violence against children and adolescents in the state of Minas Gerais, between 2009 and 2010, removed from the file of individual investigation of violence from the Notification Aggravation Information System (SINAN Sistema de Informação de Agravos de Notificação); describe the incidence, mortality and lethality of the notified cases according to types, sex, age; verify the association between the types of violence with sex and age; analyze the completeness of the filled-in items of the notification of violence file; verify the state counties which give notification of violence cases and map them out. It is an ecological study, with SINAN data base. Data analysis was made by the use of descriptive statistics; calculus of the coefficient of incidence and mortality and lethality; calculus of Relative Risk and georeferencing. 2.866 cases divided into children and adolescents have been studied. White and brown skin were predominant among the population of the study. Most cases occurred in the urban zone and at the victim s house. The major occurrence was in adolescents (54.2%) with incomplete Elementary education. The most frequent violence was physical (54.6%) and sexual (49.4%), however with higher incidence for cases of sexual abuse in females (17.4 cases/100.000 inhabitants/year). Although females were more affected, there has been lethality only (3.6%) for males in relation to physical abuse. In children, violence cases totalized 45.8 %. The most frequent were sexual (57.9%) and physical (31.1%) assaults, and the highest incidence was sexual abuse (58.4 cases/100.000 inhabitants/ year) and the most affected age was between 1 and 4 years for females. There has been association between females and most of the violence types for both groups. The most common type of physical violence was by body strength in adolescents and children (46.5% e 31.6%, respectively). Regarding sexual abuse, the most common was vaginal penetration (26.7%) in adolescents and anal (10.7%) in children. In relation to the aggressor, most were males and had not consumed alcohol. Most cases have been discharged (>70%). A lower number of counties reported violence against children and adolescents in 2009 (< 5%) compared to the year 2010 (>14.0%). There has been an increase in the notification records, yet a decrease in the information quality. It was concluded that most cases of violence occurred in adolescents and children of 1 to 4 years of age in females of white and brown skin, residents of the urban zone. The highest incidence of cases was sexual abuse.